2018
DOI: 10.17576/ajag-2018-09-10
|View full text |Cite
|
Sign up to set email alerts
|

Internet Financial Reporting (IFR) Disclosure Position and Firm Value

Abstract: Nowadays, Internet Financial Reporting (IFR) disclosure is the global way to display firm performance to investors and stakeholders. Hence, it is imperative that firms properly manage their IFR disclosure to ensure their existence is conspicuous to the world in order to foster their firm value. We believe that in order to manage IFR disclosure, firms would probably behave either ritualistically or opportunistically in terms of their IFR disclosure position. In this study, we propose a quantitative measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
(77 reference statements)
0
9
1
4
Order By: Relevance
“…Therefore, this study aims to measure the level of disclosure through OFD, which is a voluntary disclosure tool. Keliwon et al (2018) differentiate between OFD and the traditional reporting methods in terms of the methodology of reporting firms' performance. OFD disclosure consider all information that could promote the performance of firms through the internet platform, including financial and non-financial information, apart from the annual reports.…”
Section: Literature Review 21 Context Of the Studymentioning
confidence: 99%
“…Therefore, this study aims to measure the level of disclosure through OFD, which is a voluntary disclosure tool. Keliwon et al (2018) differentiate between OFD and the traditional reporting methods in terms of the methodology of reporting firms' performance. OFD disclosure consider all information that could promote the performance of firms through the internet platform, including financial and non-financial information, apart from the annual reports.…”
Section: Literature Review 21 Context Of the Studymentioning
confidence: 99%
“…These advantages have encouraged conducting investment activities and may motivate improving the IFR regulations (Shan and Troshani, 2020). Therefore, disclosing a company’s performance to stakeholders via IFR is the appropriate worldwide way (Keliwon et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using IFR also improves the integrity of financial data, which is critical for market efficiency (Haistron & Brooks, 2019). The increased usage of IFR to communicate with shareholders has reduced printed-based financial reporting since IFR attracts more potential investors (Almilia, 2009;Keliwon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As the global economy is undergoing a rapid digital transition, Internet Financial Reporting (IFR) has become the focal point for practitioners and researchers, structuring new principles on how companies function and communicate with their stakeholders (Ahmed, 2017;Cassar et al, 2019). The studies of Lymer et al (1999); Keliwon (2018) document that the application of IFR requires the use of technology, bolstered by internet-based communications and web resources, including multimedia, to disseminate financial reporting to investors, aiding them in their investment decision-making. Numerous studies have identified several advantages that can be obtained via the use of IFR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation